2010
DOI: 10.1016/j.aim.2010.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Eulerian quasisymmetric functions

Abstract: We introduce a family of quasisymmetric functions called Eulerian quasisymmetric functions, which specialize to enumerators for the joint distribution of the permutation statistics, major index and excedance number on permutations of fixed cycle type. This family is analogous to a family of quasisymmetric functions that Gessel and Reutenauer used to study the joint distribution of major index and descent number on permutations of fixed cycle type. Our central result is a formula for the generating function for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
182
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(186 citation statements)
references
References 60 publications
4
182
0
Order By: Relevance
“…This result along with q-analogs were obtained independently by several authors; see e.g. [4,16,19,21]. Roselle [18] obtained an analogous result of Eq.…”
Section: Introductionsupporting
confidence: 64%
“…This result along with q-analogs were obtained independently by several authors; see e.g. [4,16,19,21]. Roselle [18] obtained an analogous result of Eq.…”
Section: Introductionsupporting
confidence: 64%
“…The incomparability graph of P is the path G n,2 " 1´2´¨¨¨´n. Stanley [7] obtained the formula for the generating function and Haiman [5] showed that X G n,2 px, tq is e-positive and e-unimodal. (2) Let m " pm 1 , m 2 , n, .…”
Section: Definition 22 ([8]mentioning
confidence: 99%
“…Next we give the definition of the statistic admissible inversion, which was first introduced by Shareshian and Wachs [37]. Definition 3.2.…”
Section: 2mentioning
confidence: 99%